Emergence of Self-Sustained Oscillations for SIRS Model on Random Networks - Saif, Ali (Journal of Amran University, 2021)
We study the phase transition from the persistence phase to the extinction phase for the SIRS (susceptible/ infected/ refractory/ susceptible) model of diseases spreading on random networks. By studying a temporal evolution and synchronization parameter of this model on random networks, we nd that, this model on random networks, shows a synchronization phase in a narrow range of very small values of clustering coecient. This nding corroborates the conclusion reached in [Phys. Rev. Lett. 86, 2909 (2001)] that, the clustering coecient is responsible for the emergence of the synchronization phase in the small world networks. With these results and the result that we had obtained in [Physica A 535, 122251 (2019)], we give a reasonable justi cation the reason for the occurrence of that behavior, at small values of the clustering coeffcient.